Ethical Problems and Their Consequences Recognized by Novice Psychologists in Recruitment and Selection Processes [Problemas Éticos y Consecuencias Reconocidas por Psicólogos Nóveles en Reclutamiento y Selección de Personal] - Rodriguez-Araneda, M (Pontificia Universidad Catolica de Valparaiso, 2017)
Based on professional ethics in the exercise of work and organizational psychology, a qualitative research was conducted using the approach of constructivist grounded theory, with the objective of describing recognized ethical problems in recruitment and selection of personnel processes, as well as its consequences, with the participation of 40 junior Chilean psychologists. The problems recognized were discrimination, especially of gender, favor candidates and adulteration of psychological reports under pressure from clients and bosses. In the case of a fault, the most striking consequences on psychologists were negative emotions and moral distress, with little recognition of the negative impacts on candidates and organizations. When it was taken as an option not to commit a fault, the presence of sanctions for professionals was reported. The reports denote passivity and the low organizational power of the early psychologists, as well as organizational naturalization and the abusive practices of the employers.